ANALISA NILAI KALOR DAN LAJU PEMBAKARAN PADA BRIKET CAMPURAN BIJI NYAMPLUNG (Calophyllm Inophyllum) DAN ABU SEKAM PADI - Almu, M. Afif; Syahrul, S.; Padang, Yesung Allo (Universitas Mataram, 2014)
The fuel is a source of energy with greatest consumption today. Where that stock is become less until 2025th. That’s way, it must to find some new energy to replacement, that one of alternative that is a fuel of solid phase that become from briquette. The briquette that use is compound between nyamplung’s fruit and rice husk. In this case because in NTB nyamplung’s fruit and rice husk is overabundance.This research conducted three testing that are testing of heat value, testing of combustion rate, and testing of dry measure. In case where to testing of heat value using bomb calorimeter. Independent variable both of this research is combine. Between nyamplung’s fruit and rice husk with comparison 1:1, 2:1, 3:1, 1:2, and 1:3. The highest heating value is obtained from sample 3:1 as big as 4792,40 cal/gr, the lowest rate of combustion from sample 3:1 as big as 0,00156 gr/s and the lowest of dry measure lowest from sample 1:1 that is 21,52%.